Influence of cold pre-fermentation maceration on the volatilomic pattern and aroma of white wines - Alti-Palacios, Laura (2023)
Aroma compounds play a key role in wine quality due to their importance in wine aroma. The aim of the present study is to investigate the influence of cold pre-fermentative maceration (CPM) treatment on aromatic and sensory properties of white wines from four grape varieties (Tempranillo Blanco, Maturana Blanca, Viura and Garnacha Blanca) during two consecutive years (2019 and 2020). A total of 62 aroma compounds belonging to different chemical families were identified using headspace solid-phase microextraction combined with gas chromatography mass spectrometry (HS-SPME/GC-MS). CPM treatment enhanced the total relative concentration of alcohols, esters and acids compared to control wines. Regarding sensorial properties, esters made the greatest contribution to the studied white wines, mainly through the development of floral and fruity notes. On the other hand, CPM treatment did not significantly influence the total relative concentration of terpenoids, and different trends were observed according to grape variety and vintage. The obtained results showed differences in the wine’s aromatic complexity according to the grape variety, the vintage and the treatment applied and suggested that CPM treatment could represent a suitable approach to manipulate the aromatic profile and enhance the aromatic quality and complexity of wine.